2001
DOI: 10.1021/bp0100272
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Flow‐Induced Responses in Endothelial Cells

Abstract: Endothelial cells alter their morphology, growth rate, and metabolism in response to fluid shear stress. To study rapid flow-induced responses in the 3D endothelial cell morphology and calcium distribution, coupled fluorescence microscopy with optical sectioning, digital imaging, and numerical deconvolution techniques have been utilized. Results demonstrate that within the first minutes of flow application nuclear calcium is increasing. In the same time frame whole cell height and nuclear height are reduced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 98 publications
(180 reference statements)
1
28
0
Order By: Relevance
“…However, significant gaps remain in our understanding of the mechanisms that determine the spatial organization of angiogenic growth and the topology of the resulting vascular network. Although the role of biochemical factors in angiogenic growth has been studied extensively (1,11,22), very few studies have directly addressed how mechanical factors influence the topology of the vascular network.Mechanical forces affect nearly every aspect of cellular motility, metabolism, proliferation, and differentiation, and presumably the endothelial cells and pericytes that participate in the process of angiogenesis are not excluded from their effects (7,10,21,23,33,35,41). There is a tightly regulated balance between mechanical forces that are applied to the extracellular matrix (ECM) and their effects on endothelial cell phenotype (7,10,18), with the ECM mediating initial cellular mechanotransduction (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, significant gaps remain in our understanding of the mechanisms that determine the spatial organization of angiogenic growth and the topology of the resulting vascular network. Although the role of biochemical factors in angiogenic growth has been studied extensively (1,11,22), very few studies have directly addressed how mechanical factors influence the topology of the vascular network.Mechanical forces affect nearly every aspect of cellular motility, metabolism, proliferation, and differentiation, and presumably the endothelial cells and pericytes that participate in the process of angiogenesis are not excluded from their effects (7,10,21,23,33,35,41). There is a tightly regulated balance between mechanical forces that are applied to the extracellular matrix (ECM) and their effects on endothelial cell phenotype (7,10,18), with the ECM mediating initial cellular mechanotransduction (13).…”
mentioning
confidence: 99%
“…Mechanical forces affect nearly every aspect of cellular motility, metabolism, proliferation, and differentiation, and presumably the endothelial cells and pericytes that participate in the process of angiogenesis are not excluded from their effects (7,10,21,23,33,35,41). There is a tightly regulated balance between mechanical forces that are applied to the extracellular matrix (ECM) and their effects on endothelial cell phenotype (7,10,18), with the ECM mediating initial cellular mechanotransduction (13).…”
mentioning
confidence: 99%
“…10,11 Endothelial cells align parallel to the direction of unidirectional flow, through the reorganization of cytoskeletal filaments and focal adhesion complexes. [12][13][14] Fluid flow also induces secretion of vasoactive agents such as nitric oxide and prostaglandin to maintain vessel tone, 15,16 and these processes are regulated by complex signaling events. [17][18][19] Disruption of this signal process, through the oscillation of fluid flow direction 20,21 or signal pathway blockade, inhibits cell alignment, focal adhesion reorganization, and agent release.…”
mentioning
confidence: 99%
“…The surface topology of each EC is modelled as a sinusoid based on experimental measurements with atomic force microscopy (AFM) of the surfaces of ECs which have not been exposed to shear stress previously [13,62,63]. It has been observed that cell shape can change detectably within 3 min of shear exposure [64], but such changes that reflect biomolecular responses of the cell are not captured in this model. The surface function is given as [62,63] y S ¼ĥ cos (ax) cos (bz), (2:1) whereĥ is the amplitude of the surface contour.…”
Section: Geometric Modelmentioning
confidence: 99%